FINTECH BASED PEER-TO-PEER (P2P) LENDING: A PERSPECTIVE OF MSMEs IN THE NEW NORMAL OF PANDEMIC COVID-19 - Zakiyah, Tuti; Trifiyanto, Kabul; Windasari, Wahyuni (Indonesian Journal of Accounting and Governance, 2021)
The purpose of this research is to find the role of Fintech Peer to Peer (P2P) lending based on the perspective in the new normal era of Covid-19 as a financial inclusion to recovery of the MSME’ financial. The population in this study were MSMEs in Central Java and East Java Provinces. The survey method in this study used a questionnaire as a data collection tool. In addition, researchers also use purposive sampling method to determine the sample. Analysis tools for hypothesis testing using external models and E-Views 10 for evaluation of inner models. The results of this study are that peer to peer lending together has a significant effect on the interests of MSME actors in East Java in The New Normal of the Covid-19, This is also supported by a determination test value 87% Peer to peer lending fintech companies should raise perceptions consumers of the benefits, uses, benefits and risks that consumers get if using peer to peer lending fintech. One that must be done is to make consumers believe that fintech service quality peer to peer lending is much better than financial services conventional, such as banks during the Covid-19 pandemic.